From the television : an exegesis presented in partial fulfillment of the requirements for the degree of Master of Fine Art at Massey University, Wellington, New Zealand - Cartwright, Kevin (Massey University, 2017)
On the Television is presented as an immersive digital video installation that seeks to draw the viewer into the dreamlike world of the televisual. Images derived from iterative practice-based works create metaphorical foci for sociocultural archetypes and a politic of the personal. Drawn from a biographical context and primarily relying on the visual icon of the balloon, this work tests the viewer's relation to the realm of the digital screen, and offers an alternative vision for a mass media of the individual.
Keywords: Kevin Cartwright; Video art; Digital art; Mass media; Criticism and interpretation; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art